Emoji Functions in TikTok Comments on Azarine’s Brand Ambassador, Lee Min Ho - Nikita Isabel Prasetya (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study aims to analyze the emojis used in Azarine’s TikTok comments for Lee Min Ho as a brand ambassador, guided by the eight-taxonomy proposed by Yus (2014). The theory classifies the functions as: attitude signal, attitude intensity enhancer, illocutionary force modifier, humor, irony, emotion signal, parallel emotion signal, and emotion intensity enhancer. The study used 50 comments from the comments section. By using qualitative analysis, the study found that all eight emoji functions appeared in comments for Lee Min Ho. This finding suggests that fans’ responses and engagement may vary depending on how they perceive their idol or celebrity. This study highlights the importance of emojis in reflecting the audience’s attitudes toward celebrity figures on social media. Future studies could explore emoji use across other platforms, celebrity types, or cultural contexts to better understand how emojis function in different online communication settings.